Kajian Pemanfaatan Konsentrat Limbah Cair dan Abu Boiler Pabrik Kelapa Sawit sebagai Sumber Unsur Hara Tanah Ultisol - Irma Elia; Mukhlis Mukhlis; Razali Razali (Jurnal Agroekoteknologi, 2015)
Greenhouse study experiment aimed to study the utilization of waste liquid concentrates and boiler ash of palm oil mill as nutrient source of Ultisols. This study was using complete block randomized design with two factor and three replications, concentrate of waste liquid factor 0, 10, 20, 30 ton / ha and boiler ash factor 0, 50, 100, 150 kg K2O / ha. Parameters measured were soil pH, organic-C, total -N, available-P, and exchange K, plant height, shoot dry weight, root dry weight, and plant N, P, K uptake. The result of study showed that concentrate of waste liquid of palm oil mill can act as nutrient sources because increase all parameters, but boiler ash just increase soil pH, available P, exchange K and plant P uptakeKey words : boiler ash, concentrates, Ultisol.